DINAMIKA KONFLIK DI KABUPATEN POSO - Adam dam; Malkan Malkan (ISTIQRA, 2017)
Conflict is a part of human life that can not be avoided. Between conflict and consensus is like a coin, on the one hand there is a picture and on the other side there is a nominal value. Conflict and two-sided consensus that must exist in human life, as well as the presence of the people of Poso. The people of Poso have been living in a harmonious atmosphere of peace, and then have also been in great conflict. The impact of the conflict is a deep and deeply traumatic resentment and poverty in Poso society. The people of Poso continue to process the new life towards the reintegrated community as it was by making conflict as a valuable lesson for Poso society in the future